The Extremities of Literature: Traumatic Memory in Two Novels by Kazuo Ishiguro - Paola Trimarco (Text Matters, 2023)
Drawing on Michel Foucault’s description of literature as being from the outside, Catherine Malabou explains that only literature can give us access to the inconceivable space occupied by traumatic experiences. How a literary text opens such a space, one on the extremity of experience and literature itself, involves an understanding of trauma as a neurobiological wound. In this essay I will argue that what Malabou refers to as neuro-literature and her plastic reading of texts provide useful additions to current critical approaches to two of Kazuo Ishiguro’s novels that address traumatic memories. Literary critics have approached the theme of traumatic memory in Ishiguro’s work from psychological positionalities. Using psychology, like neurobiology, already suggests that a literary work can give us access to traumatic experiences. A fuller understanding of traumatic memories as manifested by Ishiguro’s writing is here viewed through the lens of neurobiology which considers the plasticity of the brain and a plastic reading of these literary texts. This paper explores two narratives driven by traumatic memories: Ishiguro’s An Artist of the Floating World (1986) and When We Were Orphans (2000), both of which address the long-term effects brought on by the trauma of war and loss.